The Role of Parental Communication in Cultivating Children's Mental Resilience with Islamic Values to Overcome Bullying - Zainul Ahwan; Putri Dewi Karfida (Communicator: Journal of Communication, 2025)
This study explores the role of parental communication in building children's self-confidence to cope with bullying in elementary school. Bullying can negatively affect children's psychological development, and self-confidence is a key factor in helping children face such challenges. Using a qualitative approach with social penetration theory, this research analyses interactions between parents and children in communication that fosters growth. Data were collected through in-depth interviews with parents and school staff. The results show that effective communication, such as giving full attention, offering positive responses, and modelling good behaviour, can enhance children's self-confidence. These findings align with Islamic teachings, emphasising the importance of excellent communication within the family, such as the Hadith, which teaches listening and setting a good example for children. Children guided with love and confidence will be better equipped to develop healthy coping strategies for bullying. This study underscores the crucial role of parents in creating a supportive environment for children's psychological development, in line with Islamic values that emphasise compassion, mutual respect, and positive communication. The implications of this study suggest the need for parenting programs that integrate effective communication and Islamic values in addressing bullying.